Development of hybrid actuation mechanism for prosthetic finger / Mohamad Amlie Abu Kasim - Abu Kasim, Mohamad Amlie (2014)
A compact and lightweight biomimetic robotic finger with dua degrees of freedom which functions closely to a biological finger has been developed. The focus is the mechatronic design of a new hybrid mechanism for the actuation of the finger joints. The hybrid mechanism consists of a DC Micromotor and a Shape Memory Alloy (SMA) actuator. By using a DC Micromotor, a high response rate as well as comparable torque and speed can be achieved at the (Metacarpophalangeal) MCP joint. By using SMA to actuate the (Proximal Interphalangeal) PIP joint, the finger configuration has been miniaturized to anthropomorphically accurate size. A customized test jig has been developed for the calibration of SMA wires. A heat sink was integrated to the rig for the purpose of cooling of SMA wires. Furthermore, a Graphical User Interface (GUI) was develop using Visual Basic.NET to control the fingers in three basic modes of operation, i.e open posture (0°), grasp posture (45°) and closed posture (90°). A functioned prototype has been built to test the hybrid actuation mechanism and the outcomes have been satisfactory.